The social brain : a developmental perspective - Decety, Jean (The MIT Press, 2020)
"This new volume brings together a range of empirical and theoretical views from both developmental psychology and developmental neuroscience, and cover a core set of questions and topics that concern the development of the social mind. The basic topics about the origins, development, and biological bases of the human social mind include, but are not limited to, face and voice recognition, attachment to others, reasoning and cognitive bias, group dynamics, theory of mind, moral evaluation, prosocial behavior, and social decision-making. Contributors from evolutionary psychology, developmental psychology, neuroscience, and behavioral economics will inform the included topics"- Resumé vydavatel